Ocular Adverse Events After COVID-19 Vaccination - Ng, Xin Le; Betzler, Bjorn Kaijun; Testi, Ilaria; Ho, Su Ling; Tien, Melissa; Ngo, Wei Kiong; Zierhut, Manfred; Chee, Soon Phaik; Gupta, Vishali; Pavesio, Carlos E; de Smet, Marc D.; Agrawal, Rupesh (Ocular immunology and inflammation, 2021)
The COVID-19 pandemic has galvanized the development of new vaccines at an unprecedented pace. Since the widespread implementation of vaccination campaigns, reports of ocular adverse effects after COVID-19 vaccinations have emerged. This review summarizes ocular adverse effects possibly associated with COVID-19 vaccination, and discusses their clinical characteristics and management. Narrative Literature Review. Ocular adverse effects of COVID-19 vaccinations include facial nerve palsy, abducens nerve palsy, acute macular neuroretinopathy, central serous retinopathy, thrombosis, uveitis, multiple evanescent white dot syndrome, Vogt-Koyanagi-Harada disease reactivation, and new-onset Graves' Disease. Studies in current literature are primarily retrospective case series or isolated case reports - these are inherently weak in establishing association or causality. Nevertheless, the described presentations resemble the reported ocular manifestations of the COVID-19 disease itself. Hence, we hypothesize that the human body's immune response to COVID-19 vaccinations may be involved in the pathogenesis of the ocular adverse effects post-COVID-19 vaccination. Ophthalmologists and generalists should be aware of the possible, albeit rare, ocular adverse effects after COVID-19 vaccination.